Human lung microvascular endothelial cells as potential alternatives to human umbilical vein endothelial cells in bio-3D-printed trachea-like structures. (April 2020) - Taniguchi, D.; Matsumoto, K.; Machino, R.; Takeoka, Y.; Elgalad, A.; Taura, Y.; Oyama, S.; Tetsuo, T.; Moriyama, M.; Takagi, K.; Kunizaki, M.; Tsuchiya, T.; et al.
Graphical abstract: Highlights: Bio-3D-printed scaffold-free structure has great potential in airway regeneration. HUVECs play an important role in bio-3D-printed structures. HMVEC-Ls can replace HUVECs as a cell source for scaffold-free structures. Some limitations in using iPSC-derived endothelial cells exist. Abstract: Background: We have been trying to produce scaffold-free structures for airway regeneration using a bio-3D-printer with spheroids, to avoid scaffold-associated risks such as infection. Previous studies have shown that human umbilical vein endothelial cells (HUVECs) play an important role in such structures, but HUVECs cannot be isolated from adult humans. The aim of this study was to identify alternatives to HUVECs for use in scaffold-free structures. Methods: Three types of structure were compared, made of chondrocytes and mesenchymal stem cells with HUVECs, human lung microvascular endothelial cells (HMVEC-Ls), and induced pluripotent stem cell (iPSC)-derived endothelial cells. Results: No significant difference in tensile strength was observed between the three groups. Histologically, some small capillary-like tube formations comprising CD31-positive cells were observed in all groups. The number and diameters of such formations were significantly lower in the iPSC-derived endothelial cell group than in other groups. Glycosaminoglycan content was significantly lower in the iPSC-derived endothelial cell group than in the HUVEC group, while no significant difference was observed between the HUVEC and HMVEC-L groups. Conclusions: HMVEC-Ls can replace HUVECs as a cell source for scaffold-free trachea-like structures. However, some limitations were associated with iPSC-derived endothelial cells.